Advance in remediated of heavy metals by soil microbial fuel cells: Mechanism and application - Sun, Yingying; Wang, Hui; Long, Xizi; Xi, Hui; Biao, Peng; Yang, Wei (Frontiers in Microbiology, 2022)
In the past decade, studies on the remediation of heavy metals contaminated soil by microbial fuel cells (MFCs) have attracted broad attention because of the self-generated power and their multifield principles such as the extracellular electron transfer (EET) reduction, electromigration for heavy metals removal. However, given the bio electro-motive power from soil MFCs is weak and fluctuated during the remediation, we need to comprehensively understand the origination of driving force in MFC based on the analysis of the fundamental rationale of ion moving in cells and improve the performance via the appropriate configurations and operations. In this review, we first described the structures of soil MFCs for heavy metals remediation and compared the advantages of different types of configurations. Then, based on the theoretical models of heavy metal migration, enrichment, and reduction in soil MFCs, the optimization of soil MFCs including the length of the remediation area, soil conductivity, control of electrode reaction, and modification of electrodes were proposed. Accordingly, this review contributes to the application of bioelectrochemistry to efficiently remove heavy metals from soils.